Theoretical modelling and FE simulation on the oblique diamond turning of ZnS crystal. (January 2016) - Zong, W.J.; Cao, Z.M.; He, C.L.; Xue, C.X.
Abstract: In diamond turning of Cleartran ZnS crystal, the input cutting parameters have significant influences on the appearance of pit or crack defects on the finished surface. Therefore, a novel oblique cutting model is developed in this work to improve the surface quality of Cleartran ZnS crystal, in which a crack-free surface is supposed to be finished in a brittle–ductile coupled mode. And subsequently, fly-cutting experiments are performed to find the brittle–ductile transition depth of Cleartran ZnS substrates, which is employed to qualitatively determine the critical uncut chip thickness and predict the critical cutting parameters, including depth of cut, tool feed rate and rake angle. Moreover, a 3D finite element cutting model of Cleartran ZnS crystal is also constructed by using the nanoindentation test and dimensional analysis method, with which the crack propagation in chip formation can be simulated. In such a way, the predicted critical cutting parameters can be validated by the cutting experiments and finite element simulation. The results show that the oblique cutting process is an effective approach to relax the critical cutting parameters and reduce the shear stress ahead of tool cutting edge, which in return heavily suppresses the crack propagation and grain breakage. As a result, the achieved surface quality is improved. Highlights: An oblique cutting model is developed to improve the surface quality of Cleartran ZnS crystal. Shear stress ahead of tool edge is a crucial factor for the crack propagation and grain breakage. Oblique cutting can release the critical cutting parameters and decrease the shear stress. A reasonable configuration of tool oblique angle is beneficial to achieving a crack-free surface.